(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
In this article the broad emphasis is on the significance of revisiting past thinking, especially from academia and in research reports of 20th century History teaching at the Further Education and Training level (FET), so as to invest in present-day youth who take History as a subject. The study is mainly qualitative, but also relies heavily on quantitative reports and the interpretation of their value regarding selective issues such as curriculum content, textbooks and teaching methodologies. In no other study so far in South Africa, has the status of the youth and History up to the present, been pinned down historically or been reviewed critically in such a way. Therefore the objective of this article is to i) record and ii) review some past thinking on teaching History to the youth with the intention of iii) learning from yesterday’s thinking and accounts. Although an effort has been made to add to the existing historiographical repertoire on the youth and History, particularly in a teaching environment, a complete historiographical review of past research contributions is beyond the scope of this article. As far as it is achievable, key moments and contributors are recalled with the intention of bringing to the reader’s attention this past historiographical repertoire as anchor for current thinking on ways of teaching History to the youth. Keywords: ; ; ; ; ; ; History and careers.